Differences in The Intention of Customers to Switch Commercial Banks in Dar Es Salaam: A Case of Tanzania Postal Bank and National Bank of Commerce - Kara, Nasra; Nzowa, Seule (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
The purpose of this study was to identify whether commercial banks customers in Tanzania had the intentions of switching banks services and examine the differences in their intentions to switch banks. The study sample included; customers banking with Tanzania Postal Bank Plc and those banking with the National Bank of Commerce in Dar es Salaam Region. Data was collected using self-administered questionnaires. Multistage sampling was employed to generate 188 respondents for the study. Descriptive statistics and an independent t-test were used to analyze the collected information. The results demonstrated that half of all the TPB Bank customers had higher intentions of switching banks than NBC customers. Additionally, the results also found out no significant differences in the intention to switch banks among commercial bank customers. This implied that bankers need to ensure that they deliver the desired services to their customers to reduce the intentions of the switchers because this would have an impact on the actual switching behaviour.